2014
DOI: 10.1109/tip.2014.2364536
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Supervised Visual Dictionary Learning by Harnessing Image Attributes

Abstract: Abstract-Bag-of-features (BoFs) representation has been extensively applied to deal with various computer vision applications. To extract discriminative and descriptive BoF, one important step is to learn a good dictionary to minimize the quantization loss between local features and codewords. While most existing visual dictionary learning approaches are engaged with unsupervised feature quantization, the latest trend has turned to supervised learning by harnessing the semantic labels of images or regions. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The regularizer (including the 2,1 -norm regularizer [57], [58], the 2 2,1 -norm regularizer [52], and the 1,∞ -norm regularizer [59]) is often used for the application of joint sparse learning. For example, the 2,1 -norm regularizer penalizes all coefficients in a whole row for jointly generating the row sparsity, please see Fig.…”
Section: B Sparse Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The regularizer (including the 2,1 -norm regularizer [57], [58], the 2 2,1 -norm regularizer [52], and the 1,∞ -norm regularizer [59]) is often used for the application of joint sparse learning. For example, the 2,1 -norm regularizer penalizes all coefficients in a whole row for jointly generating the row sparsity, please see Fig.…”
Section: B Sparse Learningmentioning
confidence: 99%
“…For example, the global feature has the ability to generalize the whole image with only a single vector so that its use in image classification is straightforward, while the local feature is calculated at multiple points (or regions) of an image so that the representation is robust to occlusion and clutter [8]- [10]. Studies have shown that only single visual feature is not always robust to all types of scenarios [11]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…al. [20] proposed a novel weakly unsupervised DL method. They incorporated cheaply available visual attributes very effectively into dictionary learning and demonstrated the efficacy, scalability of the method in large scale image retrieval and classification tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This is because it is very difficult to define suitable attributes from medical databases, which is in contrast to the databases of general images where attributes such as tree, car and feather etc can work well. Inspired by the ideas in [20], our future efforts shall attempt to identify and incorporate visual attributes into DL to improve upon the performance of CBMIR. In addition, as medical images come with different transformations (such as scaling), our future work shall further aim at addressing the invariant CBMIR with respect to other transformations as well.…”
Section: Discussionmentioning
confidence: 99%
“…Although image analysis and retrieval have been investigated for decades [16,17,39], it is still a challenging task to explore the kinship information behind face images. Recently, the abundance of face images has attracted researchers' interests to explore kinship relations based on facial appearance [21, 28-30, 32, 40, 41].…”
Section: Introductionmentioning
confidence: 99%